A true history of the United States : indigenous genocide, racialized slavery, hyper-capitalism, militarist imperialism, and other overlooked aspects of American exceptionalism - Sjursen, Daniel A. (Truth to Power, an imprint of Steerforth Press, 2021)
A combat veteran of Iraq and Afghanistan examines the history of the United States through an alternate lens that emphasizes our history of slavery, indigenous genocide, and militarist imperialism to present a more balanced view of the American story.